Single-Dose Intranasal Immunisation with Novel Chimeric H1N1 Expressing the Receptor-Binding Domain of SARS-CoV-2 Induces Robust Mucosal Immunity, Tissue-Resident Memory T Cells, and Heterologous Protection in Mice - Donghong Wang; Yao Deng; Jianfang Zhou; Wen Wang; Baoying Huang; Wenling Wang; Lan Wei; Jiao Ren; Ruiwen Han; Jialuo Bing; Chengcheng Zhai; Xiaoyan Guo; et al. (Vaccines, 2023)
Current COVID-19 vaccines can effectively reduce disease severity and hospitalisation; however, they are not considerably effective in preventing infection and transmission. In this context, mucosal vaccines are pertinent to prevent SARS-CoV-2 infection and spread. In this study, we generated a replication-competent recombinant chimeric influenza A virus (IAV) expressing the receptor-binding domain (RBD) of a SARS-CoV-2 prototype in the C-terminus of the neuraminidase (NA) of A/Puerto Rico/08/1934 H1N1 (PR8). The remaining seven segments from A/WSN/1933 H1N1 (WSN) were named PR8NARBD/WSN. We observed that the recombinant virus with the WSN backbone demonstrated improved expression of NA and RBD. A single intranasal dose of PR8NARBD/WSN(103PFU) in mice generated robust mucosal immunity, neutralising antibodies, cellular immunity, and tissue-resident memory T cells specific to SARS-CoV-2 and IAV. Importantly, immunisation with PR8NARBD/WSN viruses effectively protected mice against lethal challenges with H1N1, H3N2 IAV, and SARS-CoV-2 Beta variant and significantly reduced lung viral loads. Overall, our research demonstrates the promising potential of PR8NARBD/WSN as an attractive vaccine against emerging SARS-CoV-2 variants and influenza A virus infections.